Examining One-Star Reviews in Orthopaedic Hand Surgeons in Large U.S. Cities - Hitchman, Kyle J.; Anastasio, Albert T.; Baumann, Anthony N.; Welch, Sarah E.; Walley, Kempland C.; Klifto, Christopher S. (Journal of Wrist Surgery, 2024)
Introduction Physician-review websites are a commonly used resource by patients when choosing a surgeon. While data exist regarding some surgical specialties, no study has examined negative one-star reviews for orthopaedic-trained hand surgeons. The goal of this study was to investigate one-star reviews regarding orthopaedic-trained hand and upper extremity surgeons in the 10 largest cities in the United States to determine the associated factors behind unsatisfied patients to improve patient care.Materials and Methods Patient reviews and narratives of orthopaedic-trained hand surgeons were collected from the 10 largest cities in the United States using Vitals.com. One-star reviews (out of a five-star maximum) with comments were identified and classified as operative or nonoperative. These reviews were further subclassified based on the nature of the comment.Results A total of 830 one-star reviews with 1,662 complaints were included in this study. Of these complaints, 557 (33.5%) were from patients who received operative care and 1,105 (66.5%) were from nonoperative care patients. Nonoperative patient one-star reviews had a significantly higher proportion of complaints related to bedside manners (37.6 to 19.6%, p < 0.001), not enough time spent with the provider (18.1 to 4.5%, p < 0.001), and wait time (13.3 to 3.2%, p < 0.001) as compared with operative patient one-star reviews. Operative patient one-star reviews had a higher proportion of complaints related to disagreement with the physician's decision or plan (15.6 to 10.2%, p = 0.002); uncontrolled pain (14.4 to 7.9%, p < 0.001); and medical staff or institution (17.2 to 12.9%, p = 0.018) as compared with nonoperative patients.Discussion Most one-star reviews regarding orthopaedic-trained hand surgeons referenced nonclinical components—bedside manner was the most common complaint. It was determined that surgical patients were less likely to leave a one-star review; however, if they did, the most common complaint was in reference to a disagreement with the physician's decision or uncontrolled pain postoperatively.Type of Study Outcomes 2c.
Keywords: physician review websites; negative reviews; patients; orthopaedic surgery